2009
DOI: 10.2298/vsp0906477j
|View full text |Cite
|
Sign up to set email alerts
|

Fatal diquat intoxication

Abstract: Cardiocirculatory disturbances led to fatal complications, the heart and brain infarction. We pointed out the heart as one of the most severely affected organs in diquat poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…The herbicide diquat, which is structurally similar to paraquat, has replaced paraquat where its use has been prohibited due to a suggested association with Parkinson’s disease (McCormack et al 2002 ) and is now in widespread use as an agricultural and home use herbicide. Diquat is known to be toxic acutely in high doses (Hantson et al 2000 ; Jones and Vale 2000 ; Jovic-Stosic et al 2009 ; Saeed et al 2001 ; Schmidt et al 1999 ) and evidence of Parkinsonism after use of diquat has been suggested (Sechi et al 1992 ). Acutely, diquat causes intracerebral haemorrhage particularly in the white matter but also in the brainstem with a necrotic appearance (Vanholder et al 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide diquat, which is structurally similar to paraquat, has replaced paraquat where its use has been prohibited due to a suggested association with Parkinson’s disease (McCormack et al 2002 ) and is now in widespread use as an agricultural and home use herbicide. Diquat is known to be toxic acutely in high doses (Hantson et al 2000 ; Jones and Vale 2000 ; Jovic-Stosic et al 2009 ; Saeed et al 2001 ; Schmidt et al 1999 ) and evidence of Parkinsonism after use of diquat has been suggested (Sechi et al 1992 ). Acutely, diquat causes intracerebral haemorrhage particularly in the white matter but also in the brainstem with a necrotic appearance (Vanholder et al 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combined poisoning with diquat and glyphosate may cause severe mucosal damage including edema and hemorrhage. [4,5,17,21] Central nervous system symptoms include coma, epileptic seizures, and hemorrhage. [4,22] Shock and malignant arrhythmia may also occur in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of diquat and herbicides may cause severe and fatal poisoning. [1,35] Because of a lack of an antidote, the development of respiratory failure, renal failure, hypotension, and multi-organ dysfunction syndrome (MODS) is highly associated with poor prognosis. [69] As a technology capable of providing short-term mechanical support to the lungs, extracorporeal membrane pulmonary oxygenation (ECMO) was associated with reduced mortality in patients with very severe acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no antidote or effective treatment for DQ intoxications, the treatment being devoted to reduce absorption and/or enhance elimination. 48,50 Because DQ does not accumulate in the lungs, intensive care treatment is likely to lead to a better prognosis than PQ.…”
Section: Treatmentmentioning
confidence: 99%